2005
DOI: 10.1590/s1415-47572005000200023
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of hybrid means from a partial circulant diallel table using the ordinary least square and the mixed model methods

Abstract: By definition, the genetic effects obtained from a circulant diallel table are random. However, because of the methods of analysis, those effects have been considered as fixed. Two different statistical approaches were applied. One assumed the model to be fixed and obtained solutions through the ordinary least square (OLS) method. The other assumed a mixed model and estimated the fixed effects (BLUE) by generalized least squares (GLS) and the best linear unbiased predictor (BLUP) of the random effects. The goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…All analyses were performed using the SAS ® PROC IML program. The program to calculate BLUPs was adapted from Reis et al (2005).…”
Section: Methodsmentioning
confidence: 99%
“…All analyses were performed using the SAS ® PROC IML program. The program to calculate BLUPs was adapted from Reis et al (2005).…”
Section: Methodsmentioning
confidence: 99%
“…In the literature, the studies that use mixed linear models in annual plants are rare, being more common for the perennial plants. An example of the use of mixed models in the annual plants is the study of Reis et al (2005) and that of Bernardo et al (1996a;1996b) The data were analyzed by the methods REML and BLUP, according to Resende and Dias (2000) and Resende et al (2001). The analyses were obtained using model 23 of the software SELEGEN REML/BLUP (Resende 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The ranking of the best hybrid remained unchanged, regardless of the statistical method, trait or degree of data imbalance. Reis et al (2005), in a study with similar objectives, but using diallel analysis, also found small differences in the ranking of the best hybrids, causing no difficulties for their identification.…”
Section: Resultsmentioning
confidence: 83%
“…According to Bernardo (1996), there is a tendency to obtain higher R 2 estimates between the observed and predicted values with an increase in the number of hybrids. Reis et al (2005) investigated the causes of this correlation and identified a bias in these estimates when the sample size is small and in the absence of a cross-validation procedure. This is relevant not only to assess the ability of the model to describe the set of observed data, but, above all, its predictive reliability.…”
Section: Resultsmentioning
confidence: 99%